An Overview of the Microbiota of the Human Urinary Tract in Health and Disease: Current Issues and Perspectives - Marica Colella; Skender Topi; Raffaele Palmirotta; Donato D’Agostino; Ioannis Alexandros Charitos; Roberto Lovero; Luigi Santacroce (Life, 2023)
This article is intended to deepen our knowledge to date regarding the functions of the resident microbiota/microbiome in the urinary system for human health and disease. First, we sought to report the general characteristics (composition and stability) of the normal urinary system microbiota in the different anatomical sites in relation to some factors such as the effect of age, gender and diet, analyzing in detail the functions and the composition of the microbiota in the light of current knowledge. Several pieces of evidence suggest the importance of preserving the micro-ecosystem of the urinary system, and in some cases their relationship with diseases is important for maintaining human health is well understood. The female and male reproductive microbiota have mainly been studied over the past decade. In the past, the arrest was thought to have taken place in a sterile environment. Microorganisms of the microbiota form biofilms, three-dimensional structures, that differ in the reproductive organs and interact with both gametes and the embryo as well as with maternal tissues. These biofilms from the reproductive system also interact with others, such as that of the gastrointestinal tract. Reduction in its diversity intestinal microbiota can disrupt estrogen metabolism and affect the reproductive microbiota. It is therefore understood that its quantitative and qualitative identification is important for microbiota, but also the study of the structures formed by the microorganisms. A dysbiosis with local or systemic causes can lead to serious diseases. The role of probiotics in maintaining microbial population harmony (eubiosis) and preventing certain pathologies of the urinary and reproductive system was also investigated. A negative variation in the qualitative and quantitative composition of certain strains of microorganisms (dysbiosis) due to local or systemic causes can even lead to serious diseases. The role of probiotics in maintaining the healthy balance of microorganism populations (eubiosis), and thus in the prevention of certain pathologies of the urinary and reproductive system, has also been studied.